Effects of a lifestyle intervention on the biomarkers of oxidative stress in non-communicable diseases: A systematic review - Husain, Sarah; Hillmann, Katharina; Hengst, Karin; Englert, Heike (Frontiers in Aging, 2023)
Oxidative stress plays a critical role in the pathogenesis of chronic diseases. Therefore, improvement of oxidative stress status through lifestyle intervention can play a vital role in preventing and treating chronic diseases. This systematic review aims to provide an overview of articles published in the last decade examining the association between lifestyle intervention and oxidative stress biomarkers in the context of non-communicable diseases. The electronic databases PubMed and Web of Science were searched for relevant studies, following the PRISMA (Preferred Reporting of Systematic Reviews and Meta-Analyses) guidelines. This systematic review focused on the four important oxidative stress biomarkers; glutathione (GSH), superoxide dismutase (SOD), catalase, and malondialdehyde. 671 articles were identified, of which nine met the inclusion criteria. A trend emerged, showing that lifestyle modifications that focus on diet and physical health can improve oxidative stress in the form of an increase in superoxide dismutase and CAT levels and a decrease in Malondialdehyde levels in participants with non-communicable diseases (NCDs), GSH levels were not affected. However, the results are difficult to compare because of the heterogeneity of the methods of the biomarkers studied. Our review indicates that oxidative stress can be influenced by lifestyle modifications and may be an effective tool for the prevention and management of non-communicable diseases. This review also elucidated the importance of analyzing multiple oxidative stress biomarkers to evaluate oxidative stress, it further highlights the need to conduct long-term lifestyle intervention studies on oxidative stress biomarkers to understand the connection between oxidative stress biomarkers, NCDs and Lifestyle intervention.